Penerapan Sistem E-Voting pada Pemilihan Kepala Daerah di Indonesia (The Application of E-Voting Systems in the Local Elections in Indonesia) - Shelvie Nidya Neyman; Muhammad Fikri Isnaini; Sri Nurdiati (IPB University, 2013)
On this research, the protocol and simulation of e-voting system were designed for the local election. The functions on this system were tailored to the e-voting scheme which must meet several criterias: Eligibility, Unreusability, Anonymity, Accuracy, Fairness, Vote and Go, and Public Verifiability. The protocol which was made in this research was a system for voter registration, validation and activation voters, the election system, and the election calculation system. To maintain the security of data, the e-voting system used public key algorithm and symmetric key algorithm. The result of this research was a web-based e-voting system which runs on the computer network that meets the criteria of e-voting scheme. The result of this research showed that the e-voting process can accelerate the vote calculation and decrease human errors.Keywords: voting, e-voting, the public key cryptography algorithm, pilkada